PERSEPSI MAHASISWA DALAM PENERAPAN BLENDED LEARNING UNTUK MENDUKUNG REVOLUSI 4.0 DALAM PROSES PEMBELAJARAN DI SEKOLAH TINGGI ILMU EKONOMI GALILEO - Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
This research aims to find out how students look at blended learning and how aspects of students are required when using the e-learning type blended learning. This descriptive study was conducted with a questionnaire technique on student Prodi accounting and management of STIE Galileo selected randomly; A descriptive technique is used as a tool of analysis. The results of analysis and observation show 65% of students know blended learning, 82.1% support the implementation of blended-learning, and 64.3% expressed satisfaction with the implementation of learning with blended-learning. In addition, producing the perception of blended-learning students is beneficial, can increase motivation, make it easier to understand the material of the study, help readiness in the lecture. Based on the blended-learning analysis in the student sense has a fairly high accessibility of 71.4%, with an easy use of 75%. Good assessment students ' perception of blended-learning, giving a great role in the implementation of learning with blended-learning, which can certainly be done with adequate campus infrastructure, as well as a more interactive Siakad.